Perbedaan Likuiditas Saham Sebelum dan Setelah Penerapan Keputusan Perubahan Satuan Perdagangan (Studi Pada Emiten di JII) - Mirza Dewi Riskyta; Leo Herlambang (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
Application of unit trade change decision is one that can be used as balance information for the investors to take an investment decision. Investors must be able to analyse the signal of any information regarding the application. That signal can change of supply and demand’s shares. This study aims to find out the reaction of stock liquidity on application of unit trade change decision indicated by the difference of Trading Volume Activity (TVA) and Transaction Frequency Activity (TFA) on before and after the application of trade change decision. This study use event study approach held on 30 emiten of stock listed on Indonesia Stock Exchange period December 2013 – May 2014. This study use observation period for 11 days, are t-5 (five days before the application), t-0 (event date), and t+5 (five days after the application). Hypothesis test use paired t-test. The result based on statistical test with significance level (α) = 5% produce probability value 0.599 for TVA and 0.121 for TFA. Based on these result, it can be concluded that there is no significant difference between TVA and TFA on before and after the application of trade change decision.